**Q) Solve the following pair of linear equations:**

**ax** + **by = c**

**bx + ay = 1 + c**

**Ans: **

Given the equations:

a x + b y = c ….. (i)

b x + a y = 1 + c ….. (ii)

Let’s multiply equation (i) with a and equation (ii) with b and we get:

a2 x + ab y = a c ….. (iii)

b2 x + ab y = b + b c ….. (iv)

Let’s subtract equation (iv) from equation (iii), we get:

a^{2} x – b^{2} x = ac – b – b c

∴ x (a^{2} – b^{2} ) = c (a – b) – b

Let’s put in equation (i), we get:

**Therefore, **

**Please do press “Heart” button if you liked the solution.**